Worauf ich mich verlassen kann Kognition und Affekt in Schülereinstellungen zu Schöpfung und Evolution - Hermisson, Sabine (2023)
Along with cognitive factors, emotions and existential concerns such as the search for reassurance and autonomy shape adolescents' attitudes toward creation and evolution.